An Impact Analysis of Labor Market Programs in Hungary - Christopher J. O'Leary (W.E. Upjohn Institute for Employment Research, 1995)
This paper presents estimates of the impact of retraining and public service employment (PSE) on reemployment and earnings in the Republic of Hungary during the early phase of post-Socialist economic restructuring. Since assignment to programs resulted in groups with vastly dissimilar characteristics, impact estimates were computed using a variety of methods. Controlling for observable characteristics, retraining may have slightly improved the chances for reemployment in a non-subsidized job, but the gain in reemployment was probably not sufficient to justify the cost of retraining. However, since the durability of jobs appears to be better for those who were retrained, the long term earnings impacts may be significant. Net societal benefits from retraining could be improved by targeting services to more males, older persons, those with fewer years of formal education, and those with no non-manual specialization. PSE was a successful strategy to keep people out of unemployment, but it did not appear to be a cost effective means of getting people reemployed in non-subsidized jobs. PSE is probably best viewed as an income transfer program that has the side effect of preventing deterioration of basic work habits. In terms of reemployment, the net societal impact of PSE could be improved if it involved more older persons and females.
Keywords: J0; J4; J6; 330; labor; market; programs; Hungary; O'Leary